Answer :
Answer:
The answer is (-4) and (-7).
Step-by-step explanation:
Given;
- a₁ = 5
- a₂ = 2
- a₃ = (-1)
To Find;
- a₄ = ?
- a₅ = ?
Formula;
- aₙ = a + (n – 1) × d
Now, for common difference (d)
d = a₂ – a₁ = 2 – 5 = -3
d = a₃ – a₂ = (-1) – 2 = -3
Here, common difference is same everywhere.
So, for fourth term or n = 4
aₙ = a + (n – 1) × d
a₄ = 5 + (4 – 1) × (-3)
a₄ = 5 + 3 × (-3)
a₄ = 5 – 9
a₄ = -4
Then, for fifth term or n = 5
a₅ = 5 + (5 – 1) × (-3)
a₅ = 5 + 4 × (-3)
a₅ = 5 – 12
a₅ = -7
Thus, The fourth term is (-4) and fifth term is (-7).